Facilitating active participation in anticoagulant decisions in advanced kidney disease: co-production of a question prompt list - Kathrine Parker; Abigail Needham; Jecko Thachil; Sandip Mitra; Penny Lewis (BMC Nephrology)
Abstract Background People with chronic kidney disease are at increased risk of thrombotic and bleeding episodes making anticoagulant treatment decisions challenging. Currently, there are no support tools for people with chronic kidney disease regarding anticoagulant therapy decisions. This work aimed to co-produce materials to support shared-decision making when considering anticoagulant use in advanced chronic kidney disease. Methods Focus groups were undertaken to explore the views of people with kidney disease towards anticoagulant prescribing. Data was thematically analysed based on Makoul and Clayman’s model of shared-decision making. Co-production methods were used to develop a question prompt list based on themes from the focus groups in conjunction with people with kidney disease over three meetings. Results A question prompt list, to be used by patients when initiated on anticoagulant therapy, was co-produced. These questions were based upon participants’ experiences of the various stages of shared-decision making within the context of anticoagulant use in advanced chronic kidney disease. Of particular importance to participants was the individualised discussion around treatment risks and follow up arrangements. Conclusion Shared-decision making is important when initiating medication to ensure the best outcomes for patients, yet it can be difficult to engage in shared-decision making without prompts or guidance. This co-produced question prompt list could be included as part of national guideline to support shared-decision making for anticoagulant initiation in patients with advanced chronic kidney disease.